Anomalous Hall effect in nanoscale structures of the antiferromagnetic Weyl semimetal Mn3Sn at room temperature - Matsuo, Takumi; Higo, Tomoya; Nishio-Hamane, Daisuke; Nakatsuji, Satoru (Applied physics letters, 2022)
The magnetic Weyl semimetallic state in the chiral antiferromagnet Mn3Sn has attracted interest for its potential in memory technology. Despite vanishingly small magnetization, the material exhibits large transverse responses that can be electrically manipulated, similar to ferromagnets. Through deposition on heated Si/SiO2 substrates, we have fabricated polycrystalline Mn3Sn films that have coarse surfaces, the thinner of which have a discontinuous structure comprised of grains with diameters of the order of 100 nm. We confirm that these grains retain the anomalous Hall effect arising in the time reversal symmetry broken chiral antiferromagnetic phase of Mn3Sn at room temperature by serially connecting the grains with an additional conducting layer. These results pave the path for the potential applications of nanoscale Mn3Sn systems, which could be useful in the development of energy efficient memory devices.